Time series of basal melt rates from autonomous phase-sensitive radar (ApRES) measurements at location EIS8 on Ekström Ice Shelf, Antarctica from January 2023 to November 2023 - Ole Zeising; Daniel Steinhage; Sophie Berger; Reinhard Drews; M Reza Ershadi; Tanja Fromm; Tore Hattermann; Frank Pattyn; Olaf Eisen (PANGAEA, 2025)
The dataset consists of derived melt rates from autonomous phase-sensitive radar (ApRES) measurements. The estimated basal melt rates are based on the analysis of firn densification, strain thinning, and the change in ice thickness from the determination of vertical displacements. The basal melt rates are averaged over 7 days (moving window). To represent the variability of the melt rate on sub-weekly timescales, we also calculated the 7 day standard deviation of the basal melt rates based on a 1 day moving window. The uncertainty of the basal melt rate is based on the uncertainty of the strain estimation and the determination of the ice thickness change. Data are exported in 4 hour intervals. A positive melt rate represents melting. Details on the processing are given in Zeising et al. (2025).
In: Zeising, O et al. (2025): Time series of autonomous phase-sensitive radar (ApRES) measurements and determined basal melt rates at location EIS8 on Ekström Ice Shelf, Antarctica from January 2023 to November 2023 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972028